Glue for Sealing Internal Pancreatic Fistula in a Patient with Liver Cirrhosis: A Useful Technique - Goenka, Mahesh Kumar; Jha, Ashish Kumar; Kapoor, Nisha; Goenka, Usha (JOP. Journal of the Pancreas, 2012)
Context Pancreatic fistulae are uncommon and usually follow acute or chronic pancreatitis. While most of these are treated conservatively, some require surgery. Recently endoscopic therapy has emerged as an effective alternative treatment modality. Case report We present a patient with internal pancreatic fistula due to alcohol related chronic pancreatitis. Endotherapy using glue resulted in resolution of the fistula. Conclusion The use of endoscopic glue injection may be a safe and effective method for the successful therapy of internal pancreatic fistula.